The Process Oriented Guided Inquiry Learning (POGIL) Model and Self-Efficacy on the Science Learning Outcomes of Grade V Students - Wahyuni, I Gusti Ayu Winda Dwi; Wibawa, I Made Citra; Margunayasa, I Gede (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
The low science learning outcomes of elementary school students remain a significant problem in Education, particularly in subjects that tend to be passive and lack active student involvement. Furthermore, low levels of student self-efficacy contribute to the suboptimal understanding of science concepts. This study aims to determine the effect of the Process-Oriented Guided Inquiry Learning (POGIL) Model and self-efficacy on the science learning outcomes of fifth-grade elementary school students. The method used was a quasi-experiment with a Non-Equivalent Control Group Design. The study population was 192 fifth-grade students. A sample of 106 students was selected through a multi-stage random sampling technique, divided into experimental and control groups. Data were collected through a self-efficacy questionnaire and a multiple-choice learning outcome test. Data analysis using two-way ANOVA shows that: there are differences in science learning outcomes between students who follow the POGIL model and conventional learning, there is an interaction between the POGIL model and self-efficacy on science learning outcomes, students with high self-efficacy get better results with the POGIL model, and students with low self-efficacy also get better results with the POGIL model. In conclusion, the application of the POGIL model can improve science learning outcomes for both students with high and low self-efficacy. The implications of this study suggest that the application of the POGIL model can be an effective alternative learning strategy for improving science learning outcomes among elementary school students, regardless of their level of self-efficacy.